Elongate Twig Ant, Mexican Twig Ant (suggested common names), Pseudomyrmes gracilis (Fabricius) (Insecta: Hymenoptera: Formicidae: Pseudomyrmecinae) - Patricia L. Toth (EDIS)
EENY-418, a 5-page illustrated fact sheet by Patricia L. Toth, is part of the Featured Creatures collection. It describes this neotropical, arboreal ant best known for its associations with plants and its terrible sting, its synonymy, distribution, description, life cycle, nests, hosts, damage, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2007.